Photo-thermal aging resistant polyester composite material and preparation method thereof

By introducing modified monomers and fillers into the polyester material, and esterification polycondensation and ultraviolet light irradiation treatment, the problem of aging of polyester materials in extreme environments is solved, and its photothermal aging resistance is significantly improved.

CN119431756AInactive Publication Date: 2025-02-14JIANGXI PLASTIC HIGH-TECH MATERIALS CO LTD

Patent Information

Application Number
CN202411652139.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

At this stage, polyester materials are prone to aging in extreme environments, especially under the influence of ultraviolet rays and high temperatures, resulting in reduced performance.

Method used

Photothermal aging polyester composite materials are prepared by esterification and polycondensation of modified monomers, modified fillers, benzophenone, terephthalic acid, neopentyl glycol and other substances under specific conditions, and ultraviolet light is passed Irradiation treatment increases crosslink density.

Benefits of technology

The photothermal aging resistance of polyester composites is significantly improved, and its stability and performance retention ability in extreme environments are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a photo-thermal aging resistant polyester composite material and a preparation method thereof, a modified monomer, a modified filler, benzophenone, terephthalic acid and neopentyl glycol are subjected to esterification condensation polymerization to prepare the composite material, and the modified monomer is added, so that the prepared polyester molecule is of a branched structure; the side chain of a polyester molecule and the surface of the modified filler both contain unsaturated double bonds which can react after being irradiated by ultraviolet light, so that the number of crosslinking points of the composite material is increased, the crosslinking density is further improved, and the anti-aging effect of the material is further improved; the modified filler can improve the high-temperature-resistant effect of the composite material, the modified filler is matched with the hindered phenol structure of the side chain to further improve the heat aging-resistant effect of the composite material, hydroxyl and ketone groups on the modified filler form intramolecular hydrogen bonds, light energy can be converted into heat energy to be released, and then the light aging-resistant effect of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyester composite material preparation, and in particular to a light-heat-aging-resistant polyester composite material and a preparation method thereof. Background Art

[0002] Polyester is a type of polymer formed by the polycondensation of polyols and polyacids. This type of polymer is a thermoplastic material that can be processed into fibers, films and plastic products. Currently, most commonly used polyester materials contain benzene ring structures. The rigid conjugated system formed by the benzene ring and the ester group makes polyester have the characteristics of high tensile strength, good stiffness, resistance to burning and cracking, not easy to break, excellent electrical and optical properties, good oxygen and moisture resistance, cold and heat resistance, and excellent properties such as chemical corrosion resistance and stable shrinkage. Polyester film is mainly used in electrical, insulation, packaging, magnet containers, films, etc., and its application range is very wide. However, due to its extreme environment, affected by ultraviolet rays and high temperature, the material will age rapidly, which greatly reduces its performance and affects its normal use. Summary of the invention

[0003] The purpose of the present invention is to provide a light-heat aging resistant polyester composite material and a preparation method thereof, so as to solve the problem that the light-heat aging resistant effect of the existing polyester material is poor.

[0004] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a light-heat-aging resistant polyester composite material comprises the following steps: The modified monomer, modified filler, benzophenone, terephthalic acid, neopentyl glycol, p-toluenesulfonic acid, p-hydroxyanisole and DMF are protected by nitrogen, reacted for 1-2 hours at a rotation speed of 120-150 r / min and a temperature of 170-180° C., heated to 240-245° C., reacted for 3-5 hours at a vacuum degree of 0.3-0.5 MPa, heated to 280-285° C., reacted for 20-30 minutes at a pressure of 50-80 Pa, and irradiated with 365 nm ultraviolet light for 8-10 seconds to obtain a light-heat aging-resistant polyester composite material.

[0005] Furthermore, the amount ratio of the modified monomer, modified filler, terephthalic acid, neopentyl glycol and DMF is 3mmol:1g:10mmol:6mmol:20mL, the amount of benzophenone is 1% of the mass of the modified filler, the amount of p-toluenesulfonic acid is 5% of the mass of terephthalic acid, and the amount of p-hydroxyanisole is 1% of the mass of the modified monomer.

[0006] Further, the modified monomer is prepared by the following steps: Step A1: N-(4-hydroxyphenyl)maleimide, epichlorohydrin, boron trifluoride etherate and DMF are mixed evenly, reacted for 2-3 hours at a speed of 150-200 r / min and a temperature of 65-70°C, then sodium hydroxide solution is added, the temperature is raised to 75-80°C, and the reaction is continued for 3-4 hours to obtain intermediate 1, allyl alcohol is dissolved in chloroform, 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and triethylamine are added under stirring at a speed of 120-150 r / min and a temperature of 20-25°C, the temperature is raised to 40-50°C, and the reaction is continued for 20-25 hours to obtain intermediate 2; Step A2: The intermediate 2, tetramethylcyclotetrasiloxane, chloroplatinic acid and DMF are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 4-6 hours at a speed of 200-300 r / min and a temperature of 75-80° C. to obtain a modifier; octamethylcyclotetrasiloxane, the modifier, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out for 3-5 hours at a speed of 120-150 r / min and a temperature of 105-110° C. to obtain a diamine-terminated polysiloxane; Step A3: The diamine-terminated polysiloxane, intermediate 1 and DMF are mixed evenly, and reacted for 6-8 hours at a rotation speed of 120-150 r / min, a temperature of 60-65° C. and a pH value of 10-11 to obtain a modified monomer.

[0007] Furthermore, the amount ratio of N-(4-hydroxyphenyl)maleimide, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution in step A1 is 10 mmol:10 mmol:0.3 g:8 mL, the mass fraction of the sodium hydroxide solution is 25%, and the molar ratio of allyl alcohol, 3,5-bis(tert-butyl)-4-hydroxyphenylpropanoyl chloride and triethylamine is 1:1:1.1.

[0008] Furthermore, the molar ratio of the intermediate 2 and tetramethylcyclotetrasiloxane described in step A2 is 4:1, the amount of chloroplatinic acid used is 1‰ of the mass of tetramethylcyclotetrasiloxane, and the molar ratio of octamethylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.6:0.8:3:2.

[0009] Furthermore, the molar ratio of the diamine-terminated polysiloxane described in step A3 to the intermediate 1 is 1:4.

[0010] Further, the modified filler is prepared by the following steps: Step B1: 2, 4-dihydroxybenzophenone, triethylamine and tetrahydrofuran were mixed evenly, stirred at a speed of 120-150 r / min and a temperature of 0°C, and acryloyl chloride was added to react for 4-6 hours to obtain intermediate 3; 3-mercapto-2-(mercaptomethyl)propionic acid, intermediate 3, benzophenone and DMF were mixed evenly, and reacted for 30-40 minutes at a speed of 60-80 r / min and irradiated with 365 nm ultraviolet light to obtain intermediate 4; Step B2: The intermediate 4, 3-aminopropyltriethoxysilane, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out for 3-5 hours at a rotation speed of 200-300r / min and a temperature of 25-30°C to obtain a treating agent; graphene oxide, 3-aminopropyltrimethoxysilane, diisopropylethylamine and toluene are mixed, and the reaction is carried out for 3-5 hours at a rotation speed of 200-300r / min and a temperature of 25-30°C to obtain pretreated graphene; the pretreated graphene, the treating agent, KH570 and ethanol are evenly mixed, and the mixture is stirred at a rotation speed of 150-200r / min and a temperature of 60-70°C, and deionized water is added to react for 3-5 hours to obtain a modified filler.

[0011] Furthermore, the molar ratio of 2, 4-dihydroxybenzophenone, triethylamine and acryloyl chloride in step B1 is 1:1.1:1, the molar ratio of 3-mercapto-2-(mercaptomethyl)propionic acid and intermediate 3 is 1:2, and the amount of benzophenone is 1% of the mass of intermediate 3.

[0012] Furthermore, the molar ratio of the intermediate 4, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide described in step B2 is 1:1:1.2, the amount of 3-aminopropyltrimethoxysilane is 3% of the mass of graphene oxide, the molar ratio of diisopropylethylamine and 3-aminopropyltrimethoxysilane is 1:1, and the amount ratio of pretreated graphene, treating agent, KH570, ethanol and deionized water is 5g:3g:1g:20mL:10mL.

[0013] Beneficial effects of the invention: The light-heat aging-resistant polyester composite material disclosed in the invention is prepared by esterification and polycondensation of a modified monomer, a modified filler, benzophenone, terephthalic acid and neopentyl glycol to obtain the composite material, wherein the modified monomer uses N-(4-hydroxyphenyl)maleimide and epichlorohydrin as raw materials, and under the action of boron trifluoride ether, the hydroxyl group on the N-(4-hydroxyphenyl)maleimide reacts with the epoxy group on the epichlorohydrin, and then under the action of a sodium hydroxide solution, a new epoxy group is formed by ring closure to obtain an intermediate 1, and allyl alcohol and 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride are reacted under the action of triethylamine. The hydroxyl group on the propylene alcohol reacts with the acyl chloride on the 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride to obtain the intermediate 2. The intermediate 2 and tetramethylcyclotetrasiloxane are reacted with chloroplatinic acid to obtain the double bond on the intermediate 2 and the Si-H on the tetramethylcyclotetrasiloxane to obtain the modifier. The octamethylcyclotetrasiloxane and the modifier are ring-opened and then condensed with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to obtain the diamine-terminated polysiloxane. The diamine-terminated polysiloxane is reacted with the intermediate 1 to obtain the amino group on the diamine-terminated polysiloxane and the epoxy group on the intermediate 1 to obtain the modified monomer.

[0014] The modified filler uses 2,4-dihydroxybenzophenone and acryloyl chloride as raw materials, so that the hydroxyl group on the 2,4-dihydroxybenzophenone far away from the keto group reacts with the acyl chloride on the acryloyl chloride to obtain intermediate 3, the intermediate 3 and 3-mercapto-2-(mercaptomethyl)propionic acid are photo-reacted, so that the double bond on the intermediate 3 reacts with the thiol group on the 3-mercapto-2-(mercaptomethyl)propionic acid to obtain intermediate 4, the intermediate 4 and 3-aminopropyltriethoxysilane are reacted, so that the carboxyl group on the intermediate 4 and the 3-aminopropyltriethoxysilane are dehydrated to obtain a treated graphene, the graphene oxide and 3-aminopropyltrimethoxysilane are reacted, so that the carboxyl group on the graphene oxide and the amino group on the 3-aminopropyltrimethoxysilane are dehydrated to obtain pretreated graphene, and the pretreated graphene, the treating agent and KH570 are hydrolyzed and condensed to obtain the modified filler.

[0015] The addition of modified monomers makes the prepared polyester molecules have a branched structure, and the side chains of the polyester molecules and the surface of the modified filler contain unsaturated double bonds. After being irradiated with ultraviolet light, they can react, thereby increasing the number of cross-linking points of the composite material, thereby increasing the cross-linking density, and thus improving the aging resistance of the material. The modified monomers contain imide bonds and silicone segments, which can increase the high temperature resistance of the composite material. Combined with the hindered phenol structure of the side chain, the heat aging resistance of the composite material can be further improved. The hydroxyl and ketone groups on the modified filler form intramolecular hydrogen bonds, which can convert light energy into heat energy for release, thereby increasing the light aging resistance of the composite material. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0017] A method for preparing a light-heat-aging resistant polyester composite material comprises the following steps: The modified monomer, modified filler, benzophenone, terephthalic acid, neopentyl glycol, p-toluenesulfonic acid, p-hydroxyanisole and DMF were protected by nitrogen, reacted at a speed of 120r / min and a temperature of 170°C for 1h, heated to 240°C, reacted at a vacuum degree of 0.3MPa for 3h, heated to 280°C, reacted at a pressure of 50Pa for 20min, and irradiated with 365nm ultraviolet light for 8s to obtain a polyester composite material resistant to light and heat aging.

[0018] The dosage ratio of the modified monomer, modified filler, terephthalic acid, neopentyl glycol and DMF is 3mmol:1g:10mmol:6mmol:20mL, the dosage of benzophenone is 1% of the mass of the modified filler, the dosage of p-toluenesulfonic acid is 5% of the mass of terephthalic acid, and the dosage of p-hydroxyanisole is 1% of the mass of the modified monomer.

[0019] The modified monomer is prepared by the following steps: Step A1: N-(4-hydroxyphenyl)maleimide, epichlorohydrin, boron trifluoride etherate and DMF were mixed evenly, reacted at a speed of 150 r / min and a temperature of 65°C for 2 hours, then sodium hydroxide solution was added, the temperature was raised to 75°C, and the reaction was continued for 3 hours to obtain intermediate 1; allyl alcohol was dissolved in chloroform, 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and triethylamine were added at a speed of 120 r / min and a temperature of 20°C with stirring, the temperature was raised to 40°C, and the reaction was continued for 20 hours to obtain intermediate 2; Step A2: The intermediate 2, tetramethylcyclotetrasiloxane, chloroplatinic acid and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 200 r / min and a temperature of 75°C for 4 hours to obtain a modifier; octamethylcyclotetrasiloxane, the modifier, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 120 r / min and a temperature of 105°C for 3 hours to obtain a diamine-terminated polysiloxane; Step A3: The diamine-terminated polysiloxane, intermediate 1 and DMF were mixed evenly, and reacted for 6 hours at a rotation speed of 120 r / min, a temperature of 60° C. and a pH value of 10 to obtain a modified monomer.

[0020] The amount ratio of N-(4-hydroxyphenyl)maleimide, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution described in step A1 is 10mmol:10mmol:0.3g:8mL, the mass fraction of the sodium hydroxide solution is 25%, and the molar ratio of allyl alcohol, 3,5-bis(tert-butyl)-4-hydroxyphenylpropanoyl chloride and triethylamine is 1:1:1.1.

[0021] The molar ratio of intermediate 2 and tetramethylcyclotetrasiloxane described in step A2 is 4:1, the amount of chloroplatinic acid used is 1‰ of the mass of tetramethylcyclotetrasiloxane, and the molar ratio of octamethylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.6:0.8:3:2.

[0022] The molar ratio of the diamine-terminated polysiloxane described in step A3 to the intermediate 1 is 1:4.

[0023] The modified filler is prepared by the following steps: Step B1: 2, 4-dihydroxybenzophenone, triethylamine and tetrahydrofuran were mixed evenly, stirred at a speed of 120 r / min and a temperature of 0°C, and acryloyl chloride was added to react for 4 h to obtain intermediate 3; 3-mercapto-2-(mercaptomethyl)propionic acid, intermediate 3, benzophenone and DMF were mixed evenly, and reacted at a speed of 60 r / min and irradiated with 365 nm ultraviolet light for 30 min to obtain intermediate 4; Step B2: The intermediate 4, 3-aminopropyltriethoxysilane, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out for 3 hours at a speed of 200 r / min and a temperature of 25°C to obtain a treating agent; graphene oxide, 3-aminopropyltrimethoxysilane, diisopropylethylamine and toluene are mixed, and the reaction is carried out for 3 hours at a speed of 200 r / min and a temperature of 25°C to obtain pretreated graphene; the pretreated graphene, the treating agent, KH570 and ethanol are evenly mixed, and the mixture is stirred at a speed of 150 r / min and a temperature of 60°C, and deionized water is added to react for 3 hours to obtain a modified filler.

[0024] The molar ratio of 2, 4-dihydroxybenzophenone, triethylamine and acryloyl chloride in step B1 is 1:1.1:1, the molar ratio of 3-mercapto-2-(mercaptomethyl)propionic acid and intermediate 3 is 1:2, and the amount of benzophenone used is 1% of the mass of intermediate 3.

[0025] The molar ratio of the intermediate 4, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide described in step B2 is 1:1:1.2, the amount of 3-aminopropyltrimethoxysilane is 3% of the mass of graphene oxide, the molar ratio of diisopropylethylamine and 3-aminopropyltrimethoxysilane is 1:1, and the amount ratio of pretreated graphene, treating agent, KH570, ethanol and deionized water is 5g:3g:1g:20mL:10mL. Example

[0026] A method for preparing a light-heat-aging resistant polyester composite material comprises the following steps: The modified monomer, modified filler, benzophenone, terephthalic acid, neopentyl glycol, p-toluenesulfonic acid, p-hydroxyanisole and DMF were protected by nitrogen, reacted at a speed of 120 r / min and a temperature of 175°C for 1 hour, heated to 245°C, reacted at a vacuum degree of 0.4 MPa for 4 hours, heated to 285°C, reacted at a pressure of 65 Pa for 25 minutes, and irradiated with 365 nm ultraviolet light for 9 seconds to obtain a polyester composite material resistant to light and heat aging.

[0027] The dosage ratio of the modified monomer, modified filler, terephthalic acid, neopentyl glycol and DMF is 3mmol:1g:10mmol:6mmol:20mL, the dosage of benzophenone is 1% of the mass of the modified filler, the dosage of p-toluenesulfonic acid is 5% of the mass of terephthalic acid, and the dosage of p-hydroxyanisole is 1% of the mass of the modified monomer.

[0028] The modified monomer is prepared by the following steps: Step A1: N-(4-hydroxyphenyl)maleimide, epichlorohydrin, boron trifluoride etherate and DMF were mixed evenly, reacted at a speed of 150 r / min and a temperature of 70°C for 2 hours, then sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was continued for 3 hours to obtain intermediate 1; allyl alcohol was dissolved in chloroform, 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and triethylamine were added at a speed of 150 r / min and a temperature of 20°C with stirring, the temperature was raised to 45°C, and the reaction was continued for 23 hours to obtain intermediate 2; Step A2: The intermediate 2, tetramethylcyclotetrasiloxane, chloroplatinic acid and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 300 r / min and a temperature of 75°C for 5 hours to obtain a modifier; octamethylcyclotetrasiloxane, the modifier, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 120 r / min and a temperature of 110°C for 4 hours to obtain a diamine-terminated polysiloxane; Step A3: The diamine-terminated polysiloxane, intermediate 1 and DMF were mixed evenly, and reacted for 7 hours at a rotation speed of 120 r / min, a temperature of 65° C. and a pH value of 10 to obtain a modified monomer.

[0029] The amount ratio of N-(4-hydroxyphenyl)maleimide, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution described in step A1 is 10mmol:10mmol:0.3g:8mL, the mass fraction of the sodium hydroxide solution is 25%, and the molar ratio of allyl alcohol, 3,5-bis(tert-butyl)-4-hydroxyphenylpropanoyl chloride and triethylamine is 1:1:1.1.

[0030] The molar ratio of intermediate 2 and tetramethylcyclotetrasiloxane described in step A2 is 4:1, the amount of chloroplatinic acid used is 1‰ of the mass of tetramethylcyclotetrasiloxane, and the molar ratio of octamethylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.6:0.8:3:2.

[0031] The molar ratio of the diamine-terminated polysiloxane described in step A3 to the intermediate 1 is 1:4.

[0032] The modified filler is prepared by the following steps: Step B1: 2, 4-dihydroxybenzophenone, triethylamine and tetrahydrofuran were mixed evenly, stirred at a speed of 120-150 r / min and a temperature of 0°C, and acryloyl chloride was added to react for 5 hours to obtain intermediate 3; 3-mercapto-2-(mercaptomethyl)propionic acid, intermediate 3, benzophenone and DMF were mixed evenly, and reacted at a speed of 60 r / min and irradiated with 365 nm ultraviolet light for 35 minutes to obtain intermediate 4; Step B2: The intermediate 4, 3-aminopropyltriethoxysilane, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out for 4 hours at a speed of 200 r / min and a temperature of 30°C to obtain a treating agent; graphene oxide, 3-aminopropyltrimethoxysilane, diisopropylethylamine and toluene are mixed, and the reaction is carried out for 4 hours at a speed of 200 r / min and a temperature of 30°C to obtain pretreated graphene; the pretreated graphene, the treating agent, KH570 and ethanol are mixed uniformly, and the reaction is carried out at a speed of 150 r / min and a temperature of 65, and deionized water is added, and the reaction is carried out for 4 hours to obtain a modified filler.

[0033] The molar ratio of 2, 4-dihydroxybenzophenone, triethylamine and acryloyl chloride in step B1 is 1:1.1:1, the molar ratio of 3-mercapto-2-(mercaptomethyl)propionic acid and intermediate 3 is 1:2, and the amount of benzophenone used is 1% of the mass of intermediate 3.

[0034] The molar ratio of the intermediate 4, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide described in step B2 is 1:1:1.2, the amount of 3-aminopropyltrimethoxysilane is 3% of the mass of graphene oxide, the molar ratio of diisopropylethylamine and 3-aminopropyltrimethoxysilane is 1:1, and the amount ratio of pretreated graphene, treating agent, KH570, ethanol and deionized water is 5g:3g:1g:20mL:10mL. Example

[0035] A method for preparing a light-heat-aging resistant polyester composite material comprises the following steps: The modified monomer, modified filler, benzophenone, terephthalic acid, neopentyl glycol, p-toluenesulfonic acid, p-hydroxyanisole and DMF were protected by nitrogen, reacted for 2 hours at a rotation speed of 150 r / min and a temperature of 180°C, heated to 245°C, reacted for 5 hours at a vacuum degree of 0.5 MPa, heated to 285°C, reacted for 30 minutes at a pressure of 80 Pa, and irradiated for 10 seconds under 365nm ultraviolet light to obtain a light and heat aging resistant polyester composite material.

[0036] The dosage ratio of the modified monomer, modified filler, terephthalic acid, neopentyl glycol and DMF is 3mmol:1g:10mmol:6mmol:20mL, the dosage of benzophenone is 1% of the mass of the modified filler, the dosage of p-toluenesulfonic acid is 5% of the mass of terephthalic acid, and the dosage of p-hydroxyanisole is 1% of the mass of the modified monomer.

[0037] The modified monomer is prepared by the following steps: Step A1: N-(4-hydroxyphenyl)maleimide, epichlorohydrin, boron trifluoride etherate and DMF were mixed evenly, reacted at a speed of 200 r / min and a temperature of 70°C for 3 hours, then sodium hydroxide solution was added, the temperature was raised to 80°C, and the reaction was continued for 4 hours to obtain intermediate 1, allyl alcohol was dissolved in chloroform, 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and triethylamine were added at a speed of 150 r / min and a temperature of 25°C with stirring, the temperature was raised to 50°C, and the reaction was continued for 25 hours to obtain intermediate 2; Step A2: The intermediate 2, tetramethylcyclotetrasiloxane, chloroplatinic acid and DMF were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 300 r / min and a temperature of 80°C for 6 hours to obtain a modifier; octamethylcyclotetrasiloxane, the modifier, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide were mixed evenly, nitrogen was introduced for protection, and the reaction was carried out at a speed of 150 r / min and a temperature of 110°C for 5 hours to obtain a diamine-terminated polysiloxane; Step A3: The diamine-terminated polysiloxane, intermediate 1 and DMF were mixed evenly, and reacted for 8 hours at a rotation speed of 150 r / min, a temperature of 65° C. and a pH value of 11 to obtain a modified monomer.

[0038] The amount ratio of N-(4-hydroxyphenyl)maleimide, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution described in step A1 is 10mmol:10mmol:0.3g:8mL, the mass fraction of the sodium hydroxide solution is 25%, and the molar ratio of allyl alcohol, 3,5-bis(tert-butyl)-4-hydroxyphenylpropanoyl chloride and triethylamine is 1:1:1.1.

[0039] The molar ratio of intermediate 2 and tetramethylcyclotetrasiloxane described in step A2 is 4:1, the amount of chloroplatinic acid used is 1‰ of the mass of tetramethylcyclotetrasiloxane, and the molar ratio of octamethylcyclotetrasiloxane, modifier, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.6:0.8:3:2.

[0040] The molar ratio of the diamine-terminated polysiloxane described in step A3 to the intermediate 1 is 1:4.

[0041] The modified filler is prepared by the following steps: Step B1: 2, 4-dihydroxybenzophenone, triethylamine and tetrahydrofuran were mixed evenly, stirred at a speed of 150 r / min and a temperature of 0°C, and acryloyl chloride was added to react for 6 hours to obtain intermediate 3; 3-mercapto-2-(mercaptomethyl)propionic acid, intermediate 3, benzophenone and DMF were mixed evenly, and reacted at a speed of 80 r / min and irradiated with 365 nm ultraviolet light for 40 minutes to obtain intermediate 4; Step B2: The intermediate 4, 3-aminopropyltriethoxysilane, dicyclohexylcarbodiimide and DMF are mixed, and the reaction is carried out at a speed of 300 r / min and a temperature of 30°C for 5 hours to obtain a treating agent; graphene oxide, 3-aminopropyltrimethoxysilane, diisopropylethylamine and toluene are mixed, and the reaction is carried out at a speed of 300 r / min and a temperature of 30°C for 5 hours to obtain pretreated graphene; the pretreated graphene, the treating agent, KH570 and ethanol are evenly mixed, and the mixture is stirred at a speed of 200 r / min and a temperature of 70°C, and deionized water is added to react for 5 hours to obtain a modified filler.

[0042] The molar ratio of 2, 4-dihydroxybenzophenone, triethylamine and acryloyl chloride in step B1 is 1:1.1:1, the molar ratio of 3-mercapto-2-(mercaptomethyl)propionic acid and intermediate 3 is 1:2, and the amount of benzophenone used is 1% of the mass of intermediate 3.

[0043] The molar ratio of the intermediate 4, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide described in step B2 is 1:1:1.2, the amount of 3-aminopropyltrimethoxysilane is 3% of the mass of graphene oxide, the molar ratio of diisopropylethylamine and 3-aminopropyltrimethoxysilane is 1:1, and the amount ratio of pretreated graphene, treating agent, KH570, ethanol and deionized water is 5g:3g:1g:20mL:10mL.

[0044] Comparative Example 1 Compared with Example 1, this comparative example uses diamine-terminated polysiloxane instead of the modified monomer, and the remaining steps are the same.

[0045] Comparative Example 2 Compared with Example 1, no treating agent was added in this comparative example, and the remaining steps were the same.

[0046] Comparative Example 3 Compared with Example 1, this comparative example did not add KH570, and the remaining steps were the same.

[0047] The composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for tensile properties according to ASTM D638. The sample thickness was 2 mm, the tensile rate was 50 mm / min, and the tensile strength was tested with an irradiation intensity of 600 W / m2 The cumulative irradiation is 400kWh / m 2 , test the tensile strength after light aging, carry out hot air aging at 200℃×30 days, test the tensile strength after hot air aging, calculate the decrease rate of tensile strength after light aging and heat aging, and the test results are shown in the following table.

[0048]

[0049] It can be seen from the above table that the present invention has a good light and heat aging resistance effect.

[0050] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a light-heat-aging resistant polyester composite material, characterized in that: The specific steps include: The modified monomer, the modified filler, benzophenone, terephthalic acid, neopentyl glycol, p-toluenesulfonic acid, p-hydroxyanisole and DMF are reacted under nitrogen protection and then irradiated under 365nm ultraviolet light to obtain a light-heat aging resistant polyester composite material.

2. The method for preparing a light-heat-aging resistant polyester composite material according to claim 1, characterized in that: The usage ratio of the modified monomer, the modified filler, terephthalic acid, neopentyl glycol and DMF is 3mmol:1g:10mmol:6mmol:20mL.

3. The method for preparing a light-heat-aging resistant polyester composite material according to claim 1, characterized in that: The modified monomer is prepared by the following steps: Step A1: After N-(4-hydroxyphenyl)maleimide, epichlorohydrin, boron trifluoride etherate and DMF are mixed for reaction, sodium hydroxide solution is added, and the temperature is raised to continue the reaction to obtain intermediate 1; allyl alcohol is dissolved in chloroform, and 3,5-bis(tert-butyl)-4-hydroxyphenylpropionyl chloride and triethylamine are added after stirring, and the temperature is raised to react to obtain intermediate 2; Step A2: The intermediate 2, tetramethylcyclotetrasiloxane, chloroplatinic acid and DMF are mixed for reaction to obtain a modifier, and octamethylcyclotetrasiloxane, the modifier, tetramethylammonium hydroxide, 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and dimethyl sulfoxide are mixed evenly, and nitrogen is introduced for protection to react to obtain a diamine-terminated polysiloxane; Step A3: Mix and react the diamine-terminated polysiloxane, the intermediate 1 and DMF to obtain a modified monomer.

4. The method for preparing a light-heat-aging resistant polyester composite material according to claim 3, characterized in that: The amount ratio of N-(4-hydroxyphenyl)maleimide, epichlorohydrin, boron trifluoride etherate and sodium hydroxide solution described in step A1 is 10mmol:10mmol:0.3g:8mL, and the molar ratio of allyl alcohol, 3,5-bis(tert-butyl)-4-hydroxyphenylpropanoyl chloride and triethylamine is 1:1:1.

1.

5. The method for preparing a light-heat-aging resistant polyester composite material according to claim 3, characterized in that: The molar ratio of the intermediate 2 and tetramethylcyclotetrasiloxane described in step A2 is 4:1, and the molar ratio of octamethylcyclotetrasiloxane, the modifier, tetramethylammonium hydroxide and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is 1.6:0.8:3:

2.

6. The method for preparing a light-heat-aging resistant polyester composite material according to claim 3, characterized in that: The molar ratio of the diamine-terminated polysiloxane described in step A3 to the intermediate 1 is 1:

4.

7. The method for preparing a light-heat-aging resistant polyester composite material according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: 2, 4-dihydroxybenzophenone, triethylamine and tetrahydrofuran are mixed and stirred, and acryloyl chloride is added to react to obtain intermediate 3, and 3-mercapto-2-(mercaptomethyl)propionic acid, intermediate 3, benzophenone and DMF are mixed and reacted to obtain intermediate 4; Step B2: The intermediate 4, 3-aminopropyltriethoxysilane, dicyclohexylcarbodiimide and DMF are mixed and reacted to obtain a treating agent, graphene oxide, 3-aminopropyltrimethoxysilane, diisopropylethylamine and toluene are mixed and reacted to obtain pretreated graphene, the pretreated graphene, the treating agent, KH570 and ethanol are mixed and stirred, and deionized water is added to react to obtain a modified filler.

8. The method for preparing a light-heat-aging resistant polyester composite material according to claim 7, characterized in that: The molar ratio of 2, 4-dihydroxybenzophenone, triethylamine and acryloyl chloride in step B1 is 1:1.1:1, and the molar ratio of 3-mercapto-2-(mercaptomethyl)propionic acid and intermediate 3 is 1:

2.

9. The method for preparing a light-heat-aging resistant polyester composite material according to claim 7, characterized in that: The molar ratio of the intermediate 4, 3-aminopropyltriethoxysilane and dicyclohexylcarbodiimide described in step B2 is 1:1:1.2, the molar ratio of diisopropylethylamine and 3-aminopropyltrimethoxysilane is 1:1, and the amount ratio of pretreated graphene, treating agent, KH570, ethanol and deionized water is 5g:3g:1g:20mL:10mL.

10. A polyester composite material resistant to light and heat aging, characterized in that: Prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Optical diffusion film and preparation method thereof

    CN104459844A

  • Environment-friendly uvioresistant polyester and preparation method thereof

    CN111100266A

  • Polyester material for anti-aging film and preparation method thereof

    CN117467125A

  • Polyester resin, photo curable-thermosetting resin composition, photo curable-thermosetting layer, ink, adhesive and printed circuit board

    JP2010013527A

Cited By

  • Weather-resistant PP composite material and preparation method thereof

    CN119708700A

  • Low-warpage composite material and preparation method thereof

    CN120005412A

  • UV curing printing ink and preparation method thereof

    CN120137449A

  • High-wear-resistance thermosetting molding powder coating and preparation method thereof

    CN120137495A

  • A high wear-resistant thermosetting plastic powder coating and preparation method thereof

    CN120137495B